MASALAH MIXING DAN EXACTNESS PADA OPERATOR MARKOV CONSTRICTIVE - Sugandha, Agus (MAGISTRA, 2013)
This research will be discuss weak convergence of the sequence precompact and its properties. The convergence properties of weakly precompact sequence, can be used guarante existence of a stationary density function. Term of constrictive Markov operators guarantee existence of a stationary density. Futhermore, by using the properties of constrictive Markov operator can be shown mixing and exactness constrictive Markov operators. Keywords :constrictive Markov operator, mixing, exactnes